Economic growth combined with increased purchasing power: the effects of a policy of increasing the minimum wage on the output - Sanches, Marina da Silva; Serra, Gustavo Pereira [UNESP]; Gomes, Rikelme Duarte; Cardomingo, Matias Rebello (FapUNIFESP (SciELO), 2023)
This article analyzes the short-term economic effects of a 3.02% minimum wage adjustment based on a Social Accounting Matrix (SAM) for Brazil. The simulation exercises consider effects of income redistribution between different strata resulting from minimum wage increases by estimating the income multiplier effect, which uses different propensities to consume for each stratum. The simulated valorization is equivalent to the sum of the GDP variations in 2018 and 2019, representing a real gain in the purchasing power of the minimum wage if the adjustment in 2020 and 2021 considered the rule in force between 2011 and 2019. The results indicate possible combinations of minimum wage adjustment and fiscal policy that generate a positive net effect on economic activity (e.g., solutions mainly affecting the top of the income distribution).
Crescimento econômico combinado com maior poder de compra: os efeitos de uma política de valorização do salário mínimo sobre o produto
Keywords: fiscal policy; income distribution; minimum wage; multiplier effect; Social Accounting Matrix